As crianças de seis anos no ensino fundamental: implicações na organização do trabalho pedagógico de escolas municipais de Conceição do Jacuípe (2007-2012) - Assis, Liliane Souza de (2015)
This research discusses the implications of Law 11.274 / 06 in the organization of educational work to care for six year-old children inserted in elementary public schools in Conceição do Jacuípe, from 2007 to 2012. For this, the study elected as a matter central question: What are the implications of Law 11.274 / 2006 in the organization of educational work to care for six year-old children inserted in elementary public schools in Conceição do Jacuípe? In dialogue with this issue, this research aimed to analyze the implications of Law 11.274 / 2006 in the organization of educational work to care for six year-old children inserted in elementary public schools of Conceição do Jacuípe. The methodology is based on qualitative approach and seeks to articulate policy analysis with the processes experienced by the subjects, taking as main categories of analysis the concepts of childhood and organization of educational work. As data collection instruments, were used analysis of national and local official documents related to the object, particularly those that indicate the guidelines for education policy in the municipality, as well as semi-structured interviews with teachers who work in the first year, teaching managers and coordinators of two municipal schools, and systematic observations of educational relations established in schools in order to care for six year-old child. The data collected allow us to infer that the documents prepared by the Education City of Conceição do Jacuípe to implement the basic education of nine years, dialogue with the proposal of the law, with regard to operational aspects: a gradual transition from elementary school from eight to nine years' duration; cutting age for enrollment and the recast proposal of the organization of pedagogical work to care for six year-old children. The analysis of the processes experienced by the subjects in the law implementation process revealed the theoretical and methodological challenges that come into play, especially regarding the vagueness of childhood conception and organization of educational work in the statements of the subjects and the documents of the institutions; the fragility of discussions about the organization of the pedagogical work and its relationship with childhood specificities and the need for a debate, in the municipality, on for what and for whom we are educating.